2020
DOI: 10.3390/jcm9113553
|View full text |Cite
|
Sign up to set email alerts
|

Early Screening for Gestational Diabetes Using IADPSG Criteria May Be a Useful Predictor for Congenital Anomalies: Preliminary Data from a High-Risk Population

Abstract: Background: Our aim was to investigate whether the International Association of the Diabetes and Pregnancy Study Groups (IADPSG) glycemic thresholds used for detecting hyperglycemia in pregnancy can be predictive for malformations in women with hyperglycemia detected in early pregnancy. Methods: a single-center, retrospective observational trial of 125 mother-infant pairs from singleton pregnancies with hyperglycemia according to the IADPSG criteria diagnosed at the gestational age below 16 weeks. Glucose valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
2
9
0
1
Order By: Relevance
“…An increased rate of congenital malformations among offspring of GDM mothers was recently also demonstrated in other studies [27,28]. In a retrospective study by Zawiejska et al [27], the authors analyzed obstetric data of 125 women without PGDM but were considered to have an elevated risk for developing GDM according to Association of the Diabetes and Pregnancy Study Groups (IADPSG) criteria, or presented a fasting glycemia levels above 5.1 mmol/dL during the first trimester. They found that early fasting glycemia diagnostic for GDM (according to the IADPSG criteria) was associated with a significantly increased risk of congenital anomalies, especially cardiac malformations.…”
Section: Congenital Malformations and Diabetes In Pregnancymentioning
confidence: 86%
See 2 more Smart Citations
“…An increased rate of congenital malformations among offspring of GDM mothers was recently also demonstrated in other studies [27,28]. In a retrospective study by Zawiejska et al [27], the authors analyzed obstetric data of 125 women without PGDM but were considered to have an elevated risk for developing GDM according to Association of the Diabetes and Pregnancy Study Groups (IADPSG) criteria, or presented a fasting glycemia levels above 5.1 mmol/dL during the first trimester. They found that early fasting glycemia diagnostic for GDM (according to the IADPSG criteria) was associated with a significantly increased risk of congenital anomalies, especially cardiac malformations.…”
Section: Congenital Malformations and Diabetes In Pregnancymentioning
confidence: 86%
“…They found that early fasting glycemia diagnostic for GDM (according to the IADPSG criteria) was associated with a significantly increased risk of congenital anomalies, especially cardiac malformations. These pregnant women did not have a diagnosis of hyperglycemia before pregnancy [ 27 ].…”
Section: Congenital Malformations and Diabetes In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 125 singleton pregnancies diagnosed as eGDM (IADPSG criteria) before 16 weeks of gestation revealed that fasting hyperglycemia was associated with congenital malformation. The mean pre-pregnancy BMI of the study group was 29.1 ± 6.5 k/m 2 [ 74 ]. An OGTT conducted between 18 and 20 weeks correlated with an OGTT at 24–28 weeks and was linked to the development of LGA and neonatal hyperinsulinemia [ 75 ].…”
Section: Oral Glucose Tolerance Test For Diagnosis Of Egdmmentioning
confidence: 99%
“…This Special Issue includes various important findings. For example, Zawiejska et al show that in high-risk women, early screening for GDM using the IADPSG criteria may be a useful predictor of congenital anomalies [2]. Another study showed that inadequate gestational weight gain was very common in a large cohort of GDM with a lower risk for adverse pregnancy outcomes in women with insufficient gestational weight gain [3].…”
mentioning
confidence: 99%